Exon Snipping in Duchenne Muscular Dystrophy. Issue 3 (March 2016) - Kemaladewi, Dwi U.; Cohn, Ronald D.
Abstract : Duchenne muscular dystrophy (DMD) is a life-limiting neuromuscular disorder caused by mutations in the DMD gene encoding dystrophin. We discuss very recent studies that used CRISPR/Cas9 technology to 'snip out' mutated exons in DMD, restoring the reading frame of the gene. We also present cautionary aspects of translating this exciting technology into clinical practice.